PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PROBLEM BASED LEARNING MATERI KLASIFIKASI MAKHLUK HIDUP TINGKAT SMP - Charly Boy Mansoben; Hasminar Rachman Fidiastuti; Nugroho Aji Prasetiyo; Riantina Fitra Aldya (Inteligensi : Jurnal Ilmu Pendidikan, 2022)
This research aims to produced appropriate student worksheets on the Classification of Living Creatures material at junior high school level based on Problem Based Learning at Sunan Giri Middle School, Malang. This research was a research and development study which produces student worksheets which will be validated by material experts and media experts, then tested on 15 class VII students. The results showed that validation by material experts gave a percentage of 82%, while media experts gave 93.5%, while the results of trials by students obtained results of 90% for attractiveness and 91% for ease, with the highest percentage of statement items being student worksheets can make me understand the material easily, and the statement items in the form of LKPD make me more interested in studying science. So, it can be concluded that the LKPD based on Problem Based Learning on the Classification of Living Creatures material developed at Sunan Giri Middle School Malang was suitable for use.